2005
DOI: 10.2460/javma.2005.227.785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral rabies vaccination programs for control of rabies epizootics in coyotes and gray foxes: 1995–2003

Abstract: Data indicated that oral rabies vaccination resulted in protective immunity in a sufficient percentage of the target wildlife population to preclude propagation of the disease and provided an effective means of controlling rabies in these species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
119
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 7 publications
2
119
1
Order By: Relevance
“…Oral rabies vaccination has been successfully applied in gray foxes (Urocyon cinereoargenteus) in Texas, USA (Sidwa et al 2005), with no reported cases since May 2009 (Blanton et al 2011), until a reported case in a cow in May 2013 (E. Oertli pers. comm.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral rabies vaccination has been successfully applied in gray foxes (Urocyon cinereoargenteus) in Texas, USA (Sidwa et al 2005), with no reported cases since May 2009 (Blanton et al 2011), until a reported case in a cow in May 2013 (E. Oertli pers. comm.).…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated oral rabies vaccination (ORV) with a recombinant vaccinia-rabies glycoprotein (V-RG) vaccine Raboral V-RGH (Merial, A SANOFI Company, Athens, Georgia, USA) has resulted in canine rabies elimination in coyotes (Canis latrans; Fearneyhough et al 1998;Sidwa et al 2005), and the US was declared canine rabies free in 2008 (Velasco-Villa et al 2008). Oral rabies vaccination has been successfully applied in gray foxes (Urocyon cinereoargenteus) in Texas, USA (Sidwa et al 2005), with no reported cases since May 2009 (Blanton et al 2011), until a reported case in a cow in May 2013 (E. Oertli pers.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Cases of rabies associated with a second canine rabies virus variant found mainly in gray foxes (Urocyon cinereoargenteus) in west and central Texas have been similarly reduced. Regulations now in place in Texas and other states that prohibit translocation of certain wild animal species for hunting and other restocking purposes have reduced the likelihood of accidental introductions of rabies virus variants into unaffected areas.…”
mentioning
confidence: 99%
“…Two different rabies virus variants are present in geographically limited populations of gray foxes (U cinereoargenteus) in Arizona and Texas. Enzootic rabies among canids in southern Texas had been the result of long-standing interactions between unvaccinated domestic dogs and coyotes at the Texas-Mexico border [2][3][4][5] ; however, only 2 dogs (believed to have been translocated from outside the United States) have been reported infected with the dog/coyote rabies virus variant in Texas since 2001. On the island of Puerto Rico, another wildlife rabies reservoir exists in mongooses.…”
mentioning
confidence: 99%
“…However, oral vaccination of free-roaming dogs and other wildlife offers a cheap and efficient alternative in only a fraction of the time that is required to catch, constrain, and vaccinate by the traditional parenteral route. Edible baits containing physiological marking agents have been successfully used to vaccinate coyotes [2], raccoons [3], and dogs [4] against the spread of rabies and to vaccinate prairie dogs for plague [5]. Once the baits are consumed the marking agents may then be measured in the blood of live animals to determine the efficiency of vaccine ingestion rather than attempting to locate animals that have died of the disease.…”
Section: Introductionmentioning
confidence: 99%